Mapping Research on Human Development Index (HDI) in Indonesia (2020–2024): A Scopus based Bibliometric Study - Adimas Rois Adnan; Yolanda (Greenation International Journal of Economics and Accounting, 2025)
This study aims to analyze scientific publication trends related to the Human Development Index (HDI) in Indonesia using a bibliometric approach. Data analysis covered author distribution, institutional affiliation, subject area, country of publication, and keyword mapping visualized through VOSviewer. The findings indicate that the most active contributors are from Universitas Gadjah Mada and Universitas Indonesia, with dominant research areas including medicine, social sciences, and economics. Indonesia leads in publication output, followed by Malaysia and China. Keyword mapping reveals three major clusters: health-related terms (obesity, epidemiology, body mass index), socio-economic themes (human development index, poverty, sustainable development), and demographic aspects (human, adult, covid-19). Overall, the study concludes that HDI research in Indonesia adopts a multidisciplinary perspective, highlighting the strong interconnection between health, social, and economic dimensions in advancing human development.